The Influence Of Environmental Concern On Purchase Intention Is Mediated By Brand Trust And Willingness To Pay For Electric Cars - Andrianus Andrianus (Ridwan Institute, 2023)
Global climate change is now one of the environmental issues that is of great concern, especially in Indonesia. One of the causes of climate change is caused by transportation. This study aims to analyze the effect of environmental concerns on brand trust, willingness to pay, and purchase intention related to electric car products in Indonesia. This study uses an associative research approach with quantitative data methods. Data was collected through distributing questionnaires to car users in Indonesia via Google Forms. The data analysis technique in this study uses Structural Equation Modelling (SEM) with Smartpls 3.0 software. The results obtained in this study are a positive and significant influence for environmental concern, brand trust, willingness to pay on purchase intention, and brand trust mediates between environmental concern and purchase intention. Also, willingness to pay mediates environmental concern on purchase intention. There are also limitations in this study, such as industry limitations and a limited sampling scope. Thus, further research can examine other aspects, such as high prices, lack of charging station facilities, and limited public understanding of the benefits of electric cars.